Determination of iron-overload in thalassemia by hepatic MRI and ferritin - Angulo,Ivan L. (2008)
Accumulation of iron in thalassemia causes organ damage and reduces patient survival due to heart lesions in the second decade of life. Iron deposits are monitored by direct (biopsy) and indirect methods (ferritin) with sequential data being better than isolated measurements. This paper compares two indirect measurements of iron overload; a single hepatic iron concentration (HIC) by magnetic resonance and mean ferritin levels over four years. A retrospective study of 25 patients from the Centro Regional de Hemoterapia in Ribeirão Preto, Brazil was carried out. High HIC (above 7 mg per gram of dry weight) was found in 20 patients and high mean serum ferritin (above 2500 μg/L) in 10 patients. Stratification into three levels (low, moderate and high) of iron overload gave similar results in both tests. Many other factors influence de degree of iron overload in thalassemia. No correlation was found using a non-parametric statistical test between HIC and mean serum ferritin. Both methods provide better planning of chelation therapy.